“Propuesta promocional en redes sociales para la pertenencia de los estudiantes de la carrera de Mercadotecnia de la Universidad Técnica de Cotopaxi”. - Chango Moreta, Mónica Leticia (2024)
The present research aimed to develop a promotional proposal on social media to foster a sense of belonging among students in the Marketing program. The study addressed the analysis of the importance of promotional strategies on social media in generating a sense of belonging. To conduct the study, a quantitative methodology was adopted, with an exploratory and descriptive approach. A data collection instrument was designed with specific sections to gather demographic information, assess the use of social media, analyze content and posts, investigate events of interest, and evaluate promotional strategies. The research is grounded in a review of bibliographic sources and related projects, providing a solid conceptual foundation. A 5-point Likert scale was implemented, covering the entire population of 278 students enrolled in the Marketing program, to quantitatively assess their perceptions. Findings underscore the importance of promotion, the diversified use of social media platforms, the relevance of a sense of belonging, and other influential factors. In conclusion, the active participation of students in content creation, the diversification and updating of published material, and the constant evaluation of promotional strategies on social media to foster a sense of belonging among Marketing students were highlighted. This analysis contributed to creating a connection between students and the Marketing program, promoting a stronger sense of belonging, more effective communication, and a more enriching and participative student experience.